Rekonstruksi Sifat Melawan Hukum Pidana Materiil Dalam Undang-Undang Nomor 1 Tahun 2023 Tentang KUHP - Arifin, Setya Indra (AL WASATH Jurnal Ilmu Hukum, 2023)
The long process of legislation of the Indonesian National Criminal Code has been completed since Law Number 1 of 2023 concerning Criminal Code (National Criminal Code) was ratified and promulgated. Public criticism before National Criminal Code was ratified (when it was still in draft form) towards the existence of regulations related to the living law in society as regulated in Article 2 of the National Criminal Code, did not change anything to the regulation except for the addition of one paragraph which was originally two to three. The existence of this regulation in National Criminal Code shows the development of the legality principle that has been known in criminal law in Indonesia, namely a formal legality principle, which has developed into a material legality principle. The unlawful nature of criminal acts that originally existed as long as they were regulated in statutory rules, has now developed into not only based on written statutory rules, but also based on living law in society. By using the normative legal research method, this paper aims to demonstrate the existence of these developments while at the same time offering a reconstruction of the existing legal regulation by first examining whether the existence of the aforementioned articles is in accordance with the normative principles in the legal system in Indonesia. In fact, referring to the Constitutional Court Decision Number 003/PUU-IV/2006, the provisions of Article 2 of the National Criminal Code are no longer appropriate to defend as they are. Regulatory reconstruction efforts are needed, which in this study shows that the material unlawful nature of criminal acts needed in Indonesia now and in the future is not against material unlawful nature in its positive function, but rather in its negative function, so that the regulation of Article 2 The National Criminal Code needs to be amended and corrected immediately